Mandibular Metastasis in Neuroblastoma in a 3 Year-Old Child: A Case Report - Zineb Izi MD; Siham El Haddad MD; Tlaite Oubaddi MD; Najwa Amsiguine MD; Nazik Allali MD; Latifa Chat MD (SAGE Publishing, 2023)
Neuroblastomas commonly metastasize to the cranium and orbit, although other facial bones were less implicated. In this report we present a 3 years old child with metastatic neuroblastoma to the mandible that presented with swollen right jaw. The first assessment of the head with computed tomography revealed soft tissue mass with permeative lytic changes of the osseous structures centered on the right mandible, as well as osteo-meningitis metastases. These masses were proven to be metastatic lesions from intra-abdominal neuroblastoma of the right adrenal gland. Over the previous several years, only 29 cases of neuroblastoma metastasis to the mandible have been reported in the literature.